2016
DOI: 10.1111/jocn.13386
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative nurses' attitudes towards organ procurement: a systematic review

Abstract: Perioperative nurses play a vital role in the organ procurement procedure and require ongoing support to ensure their psychological welfare, in particular, newly qualified or inexperienced nurses' participating in organ procurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…The organ procurement procedure can be complex and encompasses a wide array of physical, mental, emotional and spiritual challenges for all participants (Gao et al., 2017, 2020). Physically, performing a few hours of surgery can be tiring; mentally, collaborating with often unfamiliar surgical teams from different hospitals can be stressful; emotionally, experiencing organ procurement can be traumatic; and spiritually, comprehending death and life can be draining.…”
Section: Resultsmentioning
confidence: 99%
“…The organ procurement procedure can be complex and encompasses a wide array of physical, mental, emotional and spiritual challenges for all participants (Gao et al., 2017, 2020). Physically, performing a few hours of surgery can be tiring; mentally, collaborating with often unfamiliar surgical teams from different hospitals can be stressful; emotionally, experiencing organ procurement can be traumatic; and spiritually, comprehending death and life can be draining.…”
Section: Resultsmentioning
confidence: 99%
“…12,13 In the course of the progression of severe neurosurgical patients, they can evolve to BD and become a PD, starting to present major hemodynamic changes that demand specific care from the multidisciplinary staff professionals, especially the nursing staff directly involved in assisting this patient. [14][15][16] When a PD is identified by one of the HTC members, nurses on call from this committee start to articulate management and assistance activities to minimize such changes and avoid the loss of this PD due to cardiac arrest. Effective management of PD prevents patient loss and minimizes the risk of injuries in transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…As healthcare professionals, nurses' attitudes toward organ procurement have the potential to influence the attitudes of patients and the general public, which might facilitate or hinder organ donation and transplantation activity. A systematic review conducted by Gao, Plummer, and Williams (2017) found that OR nurses felt distressed, emotionally isolated, and physically drained during their participation in organ procurement. Often, they are not familiar with procurement procedures (Regehr, Kjerulf, Popova, & Baker, 2004;Smith, Leslie, & Wynaden, 2015a), because such surgery is not a common procedure in the operating room.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, it was evidenced that there were few organ procurement opportunities for OR nurses to experience. Furthermore, OR nurses reportedly find it difficult to accept patients' deaths in the OR (Carter-Gentry & McCurren, 2004;Wang & Lin, 2009), and are not familiar with postmortem care, because death and death-related care are rare events in the OR (Fox, 1999;Gao et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%